التفكیر الاستدلالي وعلاقتھ بأسالیب المعاملة الوالدیة لدى طالبات المرحلة الاعدادیة - دنیا عباس جمیل (مجلة الفتح للبحوث التربوية والنفسية, 2023)
الملخص: تُعدّ مرحلة المراھقة من المراحل المھمة التي یمرّ بھا الفرد في مسیرة حیاتھ، نظرا ً لما یحدث فیھا من تغیرات بیولوجیة، وما یرافقھا من تغیرات نفسیة، وھذا ما تؤكده الكثیر من النظریات والدراسات السابقة، وبعامة فالمراھق في ھذه المرحلة یرفض السلطة الخارجیة للتحكم في سلوكھ وللحكم على تصرفاتھ إذا ما كانت صائبة أو خاطئة، فھو یعتمد على نفسھ أي على سلطتھ الداخلیة في الحكم على أفعالھ، وتتمثل ھذه السلطة عادة بالضمیر. ومن مراجعة الأطر النظریة لمجموعة من العلماء أمثال فروید وھورني وادلر وكولبرج وبیاجیھ و والترز وغیرھم فيتشك ّل الضمیر عند الفرد، وجد أنھ یتكون نتیجة للمعاملة الوالدیة التي یتعرض لھا الطفل في سنینھ الأولى، فالأسلوب الدیمقراطي والتسلطي والحمایة الزائدة والإھمال كل ّھا أسالیب تخلق الضمیر لدى الفرد ، ولكن بمستویات متفاوتة من حیث الشدة وما یرافق ذلك من شعور بالخوفو والخجل اللذان یولدان ضعف مستوى التفكیر الاستدلالي لدى الإفراد، ومن ھنا برزت مشكلة البحث الحالي وھي معرفة العلاقة بین التفكیر الاستدلالي، وأسالیب المعاملة الوالدیة لدى طالبات المرحلة الإعدادیة، لما للتفكیر الاستدلالي من تأثیر بالغ في حیاة المراھقة ، كلّ ذلك حف ّز الباحثة على إجراء بحثھا الحالي، الذي یكتسب أھمیتھ من عدة اعتبارات، أھمھا: مستوى التفكیر الاستدلالي لدى المراھقات، و تسلیط الضوء على علاقة متغیر أسالیب المعاملة الوالدیة بمتغیر التفكیر الاستدلالي الذي في ضوئھ سیتحدد أسلوب المعاملة الوالدیة المناسب للتعامل مع المراھقین وفي ضوء ما تقدم یستھدف البحث الحالي الى تحقیق الاھداف الاتیة: ١-التعرف على التفكیر الاستدلالي لدى طالبات المرحلة الاعدادیة ٢-التعرف على الاسالیب المعاملة الوالدیة لدى طالبات المرحلة الاعدادیة ٣-التعرف على علاقة التفكیر الاستدلالي باسالیب المعاملة الوالدیة لدى طالبات المرحلة الاعدادیة. - ولتحقیق أھداف البحث قامت الباحثة بعداد استبانة للتفكیر الاستدلالي ، طبّقت الفقرات على عینة ممثلة لمجتمع البحث اختیرت بالطریقة العشوائیة، تألفت من (١٠٠ (طالبة، بعدھا أجرت الباحثة تحلیل الفقرات بأسلوب المجموعتین المتطرفتین، وعلاقة درجة الفقرة بالدرجة الكلیة للمقیاس، وفي ضوء ذلك تمّ الحصول على (٢٢ ( فقرة تؤل ّف مقیاس التفكیر الاستدلالي، وقد حسب الصدق لھذا المقیاس بأسلوب الصدق الظاھري وصدق البناء، كما حسب الثبات بطریقة إعادة الاختبار ، بلغ العدد الخامس والخمسون . مجلة الفتح . ایلول لسنة ٢٠١٣ دنیا عباس جمیل -٥٠٣ - (٨٣.٠، (ومعامل الفاكرونباخ (٨٠.٠ .(ولقیاس أسالیب المعاملة الوالدیة اعتمدت الباحثة على مقیاس الربیعي (٢٠٠٧، (الذي یتأل ّف من (٢٨ (فقرة ،تعبّر عن المواقف الحیاتیة المختلفة التي یمرّ بھا الأبناء ، موز ّعا ً علیھا البدائل الخمسة المتمثلة الأسالیب الخمسة للمعاملة الوالدیة (الدیمقراطي،والتسلطي، والحمایة الزائدة،التذبذب ، والإھمال) ،تمث ّل ردة فعل الوالدین في تلك المواقف وكما یدركھا الأبناء، ویختار الفرد أسلوب معیّن لكلّ موقف. وتبیّن من نتائج البحث وجود علاقة إیجابیة دالة إحصائیا ً بین التفكیر الاستدلال والأسلوب الدیمقراطي والمتذبذب الذي یتبعھ الوالدان مع أفراد العینة ،وفي ضوء ھذه النتائج خرجت الباحثة بعدد من التوصیات والمقترحات. ١ -القیام بدراسة للتفكیر الاستدلالي وعلاقتھ بأسالیب المعاملة الوالدیة لطلاب المرحلة المتوسطة، والإعدادیة الذكور . ٢-القیام بدراسة للتعرّف على التفكیر الاستدلالي وعلاقتھ بمتغیرات اخرى لدى طلبة الجامعة. ٣ -القیام بدراسة للتعرّف على العلاقة بین متغیر التفكیر الاستدلالي وسمات الشخصیة لدى طلبة المرحلة الإعدادیة. Abstract: The adolescence of milestones experienced by the individual in his career, in view of what is happening where changes biological weapons, and the accompanying psychological changes, and this is confirmed by a lot of theories and previous studies, and general Valemraehg at this stage to reject the authority of Foreign Affairs to control his behavior and sentenced to his actions if it was right or wrong, it depends on himself any authority to rule on internal actions, and represented the power normally conscience. The review of theoretical frameworks to a group of scientists, such as Freud, Horney and Adler and Kohlberg and Piaget and Walters and others to form the conscience of the individual, was found to be composed as a result of the treatment of parental suffered by the child in Sneineh First, Valoslob democratic and authoritarian and extra protection and neglect are all methods create conscience of the individual, but varying levels in terms of intensity and is accompanied by a sense of Balkhovo and shame which generate twice the level of thinking deductive among individuals, hence emerged the problem of current research is to know the relationship between thinking العدد الخامس والخمسون . مجلة الفتح . ایلول لسنة ٢٠١٣ دنیا عباس جمیل -٥٠٤ - inferential, and methods of treatment parenthood has schoolers prep, what to think indicative of a significant impact on the lives of adolescence, all that stimulating researcher on the current examination procedure, which acquires its importance from several considerations, including: the level of deductive thinking among adolescents, and highlight the relationship variable variable parental treatment methods deductive thinking that in the light of which will be determined appropriate parentaltreatment method for dealing with teenagers In light of the foregoing current research targets to achieve the following objectives: 1 - Identifying the deductive thinking among middle school students 2 - Get the parental treatment methods middle school students 3 - Get a relationship thinking deductive with parental-treatment methods with middle school students. - To achieve the objectives of the research, the researcher counter questionnaire to think inferential, applied paragraphs on a representative sample of the research community chosen randomly, consisted of (100) student, then conducted a researcher analyzing paragraphs style groups, and the relationship between the degree of paragraph primarily the overall scale, and in that light was obtained (22) paragraph constitute a measure inferential thinking, honesty has been calculated for this measure in a virtual honesty and sincerity construction, and according to retest stability in a way, was (0.83), and coefficient ٠.٨٠)). To measure the methods of treatment of parental adopted researcher on a scale Rubaie (2007), which consists of (28), paragraph expresses the life situations of various experienced by children, distributed by alternatives five of the methods of the five treatment of parental (democratic and authoritarian, and extra protection, oscillation, and neglect), represents the reaction of the parents in these situations, as perceived by children, and chooses a particular method for each individual position. The results of research and a statistically significant positive relationship between thinking and reasoning and democratic العدد الخامس والخمسون . مجلة الفتح . ایلول لسنة ٢٠١٣ دنیا عباس جمیل -٥٠٥ - method wobbler which parents followed with the sample, and in the light of these results came researcher with a number of recommendations and proposals. 1 - to do a study of deductive thinking and its relationship to parental treatment methods for students Intermediate, and junior high boys. 2 - carry out a study to identify the deductive thinking and its relationship with other variables among the students of the university. 3 - carry out a study to identify the relationship between the variable deductive thinking and personality traits among middle school students.